PERBANDINGAN PULAU BALI DAN PULAU JEJU DALAM BIDANG PARIWISATA - Ummul - Hasanah; Yuniastuti Eka Hapsari (Sekolah Vokasi Universitas Gadjah Mada, 2018)
There are some similarities and differences between Bali and Jeju in tourism sector. Similarities and differences of the two islands consist of the early history of the development of tourism and their tourist attractions. Bali and Jeju are both became famous around the world because of a book written by foreigners. Besides of the history of tourism, both islands have similarities in the tourist attractions. If in Bali there is Desa Penglipuran, in Jeju there is Seongup Jeju Folk Village. Both villages are tourist villages which still retain their original culture. In addition to similarities in these two islands, there are also differences of Bali and Jeju. Started by the early history of the development of tourism, Bali Island from the beginning is famous for its natural beauty as a tourist destination, Jeju on the other hand, need to experience several incidents to finally become a popular tourist destination. As for the tourism attractions, compared to Bali, tourist facilities in Jeju are better, for example in Woljeongri Beach in Jeju, tourists who want to play canoe will be provided a safety life jacket, but in Sanur, Bali, visitors are not provided those facilities. Besides of those examples, there are some other similarities and differences of the two islands.